Outcome of childhood malignancies at the University of Port Harcourt Teaching Hospital: a call for implementation of palliative care - Eke, Gracia K (Afr Health Sci, 2016)
BACKGROUND: Cancers in children are yet to be recognised as an important cause of childhood morbidity and mortality in developing countries where more than 70% of the world annual cases occur. Despite the limited resources and whatever the projected outcome, children with cancer need treatment, be it curative or palliative. OBJECTIVES: To determine outcome of cancers in children at the UPTH; identify factors that influence outcome, highlight the need for palliative care. METHOD: A retrospective study of cases of childhood malignancies admitted into Paediatric Oncology unit of UPTH over a two year period. Clinical profile of patients and outcome were analyzed using SPSS version 20.0. RESULTS: Sixty cases were analysed: 35(58.3%) males, 25(41.7%) females giving a M:F ratio of 1.4:1. Under-fives constituted 55%. Twenty-seven (45%) patients presented within 4 weeks of onset of symptoms. Median duration of symptoms before presentation was 8 weeks while 36 (60%) had metastatic disease at diagnosis. Twenty patients (33.3%) defaulted with or without specific treatment. Mortality was recorded in 26(43.4%) of cases. CONCLUSION: There were more cases of cancer amongst under-fives with male preponderance. Late presentation, financial constraints and high default rate were contributory factors to poor outcome in most cases. Lack of palliative care left many families to face their sufferings.